The Relationship between Health Service Quality and Satisfaction Level of JKN SJSN (Public Health Security) Patient in UPTD Puskesmas Nusukan of Surakarta City - Hanni Wardhani; Bhisma Murti; Ruben Dharmawan (Nexus Kedokteran Komunitas, 2015)
JKN SJSN (Public Health Security) patient as the customers who use health care service in Puskesmas need a high-quality health service to cure the diseases they suffer from. Furthermore, to generate satisfaction with the health service they receive from the personnel of Puskesmas. As we know, Puskesmas is one form of comprehensive health service organizations encompassing health promotion, prevention, curing and recovery aspects for all people so that the society will get a high-quality and affordable health service. This study aimed to analyze the relationship between health service quality and the satisfaction level of JKN SJSN patients in UPTD Puskesmas Nusukan of Surakarta City. This study was an analytical observational research with cross-sectional approach. Fourty subjects of research selected using simple random sampling technique were the participants of JKN SJSN who had had them examined in UPTD Puskesmas Nusukan of Surakarta City and met the inclusion criteria. The data collection was carried out through questionnaire with the direction of the researchers. The data of research was analyzed using Chi Square test and processed using Statistical Product and Service Solution (SPSS) 21.00 for Windows. This study showed that the Quality of Health Service was related significantly to the Satisfaction Level of JKN SJSN Patient. There was a statistically significant relationship between Health Service Quality and the Satisfaction Level of JKN SJSN patients with OR = 20,8; CI 95% = 2,35184,40; p<0,001.